New botánica reccords for La Pampa province (Argentina) (Semiárida, 2020)
Blackstonia perfoliata, Huds. (Gentianaceae) y Samolus valerandi L. (Primulaceae), new records for La Pampa province are reported with information about life forms, habitat and common names.
Keywords: New records; Blackstonia perfoliata; Samolus valerandi; La Pampa; Flora